2014
DOI: 10.1039/c4ta00899e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of core–shell structured mesoporous silica nanospheres with dually oriented mesochannels through pore engineering

Abstract: Core–shell structured mesoporous silica nanospheres with penetrating mesochannels in the core and radial mesochannels in the shell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Size and wrinkled structures of WSNs are sensitive to the molar ratio of CTAB to PVP. This finding is consistent with previous results [27].…”
Section: Resultssupporting
confidence: 96%
See 2 more Smart Citations
“…Size and wrinkled structures of WSNs are sensitive to the molar ratio of CTAB to PVP. This finding is consistent with previous results [27].…”
Section: Resultssupporting
confidence: 96%
“…2d and S2d) and radially align toward the edge of surfaces because of restrictive power, strong selective adsorption, and molecular self-assembly of PVP molecular chains [37][38][39]. This property may facilitate the diffusion of the guest molecules throughout the WSNs [27]. Mesostructures of mesoporous silica spheres prepared at different ratios of CTAB to PVP can be further verified by small-angle XRD patterns (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Third, MSNs with larger pores in the cores and smaller pores in the shells were synthesized by adding TMB in the core formation step and by adding additional CTAB in the shell formation step. Although pore size expansion of mesoporous silica by adding pore-expanding agents such as TMB, alkylamines, and toluene has been reported [27][28][29][30], we propose a novel approach for the successful preparation of core-shell MSNs with bimodal pore structures. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, Peng et al investigated the effect of the amount of trimethylbenzene on various parameters, such as hydrodynamic diameter and pore size, which will enable us to prepare colloidal MSNs with desired pore sizes and structures. 339 On the other hand, we used triisopropylbenzene as a swelling agent instead of trimethylbenzene. 346 We found that this swelling agent has a stronger ability to cause the swelling of the surfactant micelles.…”
Section: Soft Template;mentioning
confidence: 99%